Mandibular Plasmocytoma: A Case Report of a Rare Entity - Alejandro Cedeño; Gustavo Bustamante; Ariamay Castrillo; Salomon Ramos (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
A plasmacytoma is a rare malignant, unifocal, monoclonal, neoplastic plasma cell proliferation tumor that usually occurs within the bone. In soft tissue, it is often seen, in which case the term extramedullary plasmacytoma is used. Some researchers believe this lesion is the least aggressive part of a plasma cell neoplasm spectrum that extends to multiple myeloma. The diagnosis of Solitary Plasmacytoma of Bone (SPB) is established by histopathological examination, and the histopathological presentation is identical to that of multiple myeloma. We present a case of a 55-year-old patient with the increased facial volume on the left side and a year of evolution, intraorally with exophytic and erythematous lesions and pseudomembranous plaques in the jaw on the left side, which at histopathological study resulted in plasmacytoma. The diagnosis was confirmed by immunohistochemistry. Oral and maxillofacial surgeons should know about this disease's etiology and clinical characteristics, and the oral cavity presence since a late treatment compromises the patient's life.